Persepsi User Iphone Terhadap Kebijakan Pemerintah Atas Pembatalan Rilis Iphone 16 di Indonesia - Febrina, Mitha; Fajrian, Subhan; Azzahra, Syakila; Gifarly, Rayhan Akbar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Apple company is rumored to be releasing the next series of the technology they developed, namely the iPhone 16, in Indonesia in 2024. However, the release did not go as smoothly as expected, with many obstacles and challenges that had to be faced. The case is not without reason but is based on regulations issued by the government, which is one of the main reasons why Apple has not yet officially released and freely sold its products in Indonesia, as it has not met the Domestic Component Level (TKDN) requirements set by the government. According to the Ministry of Industry, Apple must achieve a Domestic Component Level (TKDN) of 40% and fulfill an investment commitment of Rp 1.71 trillion, of which they have only realized Rp 1.48 trillion. In addition, the validity period of Apple's TKDN certificate has also expired, so they need to extend it by fulfilling the remaining investment of Rp 240 billion. Without that certificate, all iPhone 16 products are considered illegal to sell in Indonesia. Through the descriptive qualitative research method, the researcher explores perceptions among the public, especially iPhone users, regarding the cancellation of the iPhone 16 release in Indonesia. Through several in-depth interviews, data collection techniques, media monitoring, and field observations. It was found that speculation arose that the policy created injustice, especially for consumers who had been waiting for a long time. On the other hand, some understand the government's move as appropriate, wise, and firm in encouraging investment from foreign companies like Apple. The results and discussion show that this perception is not only influenced by economic factors but also by the social value and status attached to iPhone ownership.